EFFICACY OF PHOTODYNAMIC THERAPY IN THE TREATMENT OF PURULENT-INFLAMMATORY DISEASES - Boboev, K.Kh.; Muzaffarov, N.S. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Photodynamic therapy is a part of photochemotherapy, in which, in addition to light and the drug, oxygen is needed. The mechanisms of the cytotoxic effect of photodynamic therapy have been shown in detail in the works of T.J. Dougherty and can be presented as follows. Photosensitizer molecules introduced into the body are selectively fixed on cell membranes and mitochondria. Moreover, the maximum concentration of the drug in the tissues is reached after 24-72 hours. When photosensitized tumor tissue is irradiated with laser radiation, there is a transition of non-toxic triplet oxygen into singlet oxygen, which has a pronounced cytotoxic effect, which leads to the destruction of the cell membranes of tumor cells. This review article is devoted to the effectiveness of photodynamic therapy in the treatment of purulent-inflammatory diseases.